Pengaruh Transformational Leadership Style, Organizational Commitment, Dan Employee Engagement Terhadap Employee Performance - Kenyshia Afifah Disty Rahmadhani; Mirzam Arqy Ahmadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of transformational leadership style, organizational commitment, and employee involvement on employee performance. With a quantitative approach, data was collected through a survey involving employees from DJP Central Java II. This research method is quantitative. The population of this research is all 130 employees of DJP Central Java II. The sampling technique in this research is non-probability sampling. The sampling technique used was purposive sampling, the number of samples obtained in this study was 130 respondents. The data needed in this research is primary data. The primary data needed in this research was obtained through distributing questionnaires which were distributed to respondents at DJP Central Java II. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The research results show that transformational leadership style and employee involvement have a significant influence in improving employee performance. In addition, organizational commitment functions as a strengthening relationship between leadership and employee engagement, which indirectly influences performance. This study emphasizes the importance of the role of adaptive leadership and employee involvement in creating a productive work environment resulting in effective and efficient employee performance.